The woman in prison under the gaze of scientific production (Research, Society and Development, 2022)
This study aims to analyze the social representations of female sexuality in the penitentiary system present in scientific studies. It is a systematic literature developed from the study of theses and dissertations cataloged in the Brazilian Digital Library of Theses and Dissertations (BDTD). It is based on the studies carried out based on the theory of social representations. The searches were carried out using the keywords: inmates; fangs; female prisoners; deprivation of liberty; female incarceration; women; prison; incarcerated women; prison system; closed regime; genre; visit and intimate encounter; family visit; intimate visit; visit; intimate encounter; and affective relationships. The inclusion criteria were: Brazilian theses and dissertations, on visits and intimate encounters in women's prisons, without restriction regarding the methodological design or publication period. And exclusion: theses and dissertations that are not related to intimate visits to women deprived of their liberty and repeated productions. As a final result, 7 publications were obtained (2 theses and 5 dissertations). The results indicate the scarcity of works that portray women in detention in the face of visits and intimate encounters, reaffirming gender violence and the invisibility of women, who, in addition to being deprived of their freedom, are also deprived of their sexuality, not being considered a right, but rather a condition. If making it necessary to develop more studies on the subject, to expose the problems and ensure the rights of women.